Compliance of anti-rabies vaccine among dog bite victims in an urban slum of Chennai: a cross sectional study - R., Shivasakthimani; Chellaiyan D., Vinoth Gnana; G., Ravivarman; R., Murali (International Journal Of Community Medicine And Public Health, 2018)
Background: Among infectious disease, rabies has the highest case fatality rate. The major problem of rabies is attributable to its dog-mediated transmission which is an impending threat to more than 3.3 billion people. Poor compliance of vaccine increases the mortality rate due to rabies. The present study attempts to ascertain pattern of dog bite and compliance to post exposure prophylaxis. Methods: This cross sectional study was carried out in Primary Health Centre in an urban slum of Chennai in Tamil Nadu. The study included 301 dog bite victims residing in urban slum with wound categories II & III (as per WHO). A pretested, semi-structured questionnaire was used for data collection. Data was analysed with SPSS-IBM (version 21.0). Chi-square test was applied. Results: Mean (SD) age of study participants was 28 (±16.3) years. Males were 176 (58.5%) and females were 125 (41.5%). Among the bites, pet dog bites were 140 (46.5%), and stray dog bites were 161 (53.5%). Majority of the bites 161 (53.5%) were unprovoked, category II bites were 216 (28.2%).Compliance up to 3 dose was found in 213(70.8%). Association was found between site of the dog bite and compliance of anti- rabies vaccine (p=0.021). Conclusions: Despite the availability of costless vaccines in public health care system, the compliance rate is only moderate. Health education about the vaccination after dog bite needs to be imparted among the community to reduce the rabies related mortality rate.